Model development for estimating sales adjusment magnitude in real estate appraisal using hedonic price model and paired data analysis - Bagaskara, Bagaskara; Prativi, Fatima Putri (Universitas Ahmad Dahlan, 2025)
This study aims to develop a model that can identify a reference for determining the adjustment magnitude in the market approach used in appraisal practice. Currently, it is challenging for appraisers to accurately determine the extent of these adjustments. Data collection in this study employed purposive sampling, ensuring that the criteria and specifications closely mirrored the data collection process in appraisal practices. The researcher selected three districts to capture any possible variations in location affecting the adjustment magnitude. The collected data was regressed to build a hedonic price model, which was later analyzed using the paired data analysis method to meet ideal model conditions and specifications. The results of this study demonstrate that the adjustment magnitude in the market approach can be identified from price differences resulting from variations in a single attribute. The highly heterogeneous housing market conditions in Indonesia present significant challenges for conducting paired data analysis in a practical context. Artificial conditions were required to meet the specifications for paired data analysis. The implication of the study that appraisers in determining adjustments in the market approach. Additionally, the model/procedure developed in this study can be applied in research across different contexts and objects, contributing to the advancement of real estate valuation science.